HUBUNGAN MOTIVASI DAN DUKUNGAN KELUARGA DENGAN KEINGINAN MAHASISWA S1 KEPERAWATAN SEMESTER 8 UNTUK MENERUSKAN PROGRAM PROFESI NERS - Perceka, Andhika Lungguh (Universitas Pendidikan Ganesha, 2020)
This research aims to seek the association of Motivation and support of the family with the wishes of students of bachelor degree of nursing in 8th semester to continue college to the profession ners in Stikes karsa husada Garut. Design Analytic descriptive analytics using the cross sectional approach. In this research, all students in bachelor degree of nursing in 8th semester as much as 100 people become population. The results of the study obtained the relationship between motivation with the desire to proceed to the profession with the level of p Value 0.030, and there is a connection between skills with students motivation 8th semester with the status of p value = 0.031. And a significant association of family support with the desire to continue the profession of Ners with a status of P Value 0.047